Microglia activation in the mPFC mediates anxiety‐like behaviors caused by Staphylococcus aureus strain USA300. Issue 9 (17th August 2022) - Zou, Jiao; Shang, Weilong; Yang, Ling; Liu, Tianyao; Wang, Lian; Li, Xin; Zhao, Jinghui; Rao, Xiancai; Gao, Junwei; Fan, Xiaotang
Abstract: Introduction : Staphylococcus aureus ( S. aureus ) is considered as one of the major causative agents of serious hospital‐ and community‐acquired infections. Recent studies have reported that S. aureus infection induced neuroinflammation and was linked with some mental disorders. To evaluate the effects of S. aureus infection on abnormal behaviors, we conducted the present study. Methods : A S. aureus USA300‐infected mouse model was established using bacterial suspension injection into tail vein. A series of behavioral tests were performed after USA300 infection. The expression of cytokines was detected in serum and mPFC. The number and some morphological parameters of microglia were also evaluated by immunofluorescence staining. Results : Anxiety‐like behaviors, instead of locomotor activity impairment or depression‐like behaviors, were observed in mice infected with S. aureus USA300 compared with control. S. aureus USA300 infection caused overexpression of IL‐6, TNF‐α, and IL‐1β in serum, resulted in microglial over‐activation and excessive release of proinflammatory cytokines in the mPFC. In addition, overexpression of TLR2 accompanied by increased GLS1 and p‐STAT3 was observed in the mPFC of mice infected with S. aureus USA300. Conclusion : This study provides evidence that S. aureus USA300 infection can lead to neuroinflammation in the mPFC of mice, which may contribute to the development of anxiety.